Reassessing the impact of the Pantawid Pamilyang Pilipino Program results of the third wave impact evaluation - Orbeta, Aniceto C. Jr; Melad, Kris Ann M.; Araos, Nina Victoria V. (Research paper series, 2023)
The Pantawid Pamilyang Pilipino Program is the government’s primary social protection strategy to break intergenerational poverty by supporting poor households and investing in children’s health and education. Previous impact evaluations demonstrated the program’s success in keeping children healthy and in school. This third impact evaluation seeks to reevaluate the program’s impact on short-term and intermediate outcomes related to health, education, household welfare, and other sociobehavioral domains. The evaluation employs regression discontinuity design to compare the program’s impact on treatment households (Pantawid beneficiaries) and comparison households (non-Pantawid beneficiaries) within specific bandwidths of distance from the poverty threshold that determines program eligibility. Results indicate that the program still positively impacts most of the target education and health outcomes of children and pregnant women. In addition, the program positively impacts household welfare, community participation, awareness of basic means to mitigate vulnerabilities, and children’s grit or determination. However, some results are inconsistent with previous evaluations, such as the negative impact on some nutrition outcomes, maternal healthcare service usage variations, and an insignificant reduction in child labor incidence. The study recommends improving program monitoring, strengthening enforcement of health conditions, and further researching the factors driving some of the unexpected results. It also suggests adjusting program policies or incentives, particularly in terms of reevaluating the cash grant value and using the program’s positive impacts on the behavior of children and adults as a model for other interventions. --Back cover.